Clinical control in COPD and therapeutic implications: The EPOCONSUL audit - Myriam Calle Rubio; Marc Miravitlles; Juan José Soler Cataluña; José Luis López-Campos; Bernardino Alcázar Navarrete; Manuel E. Fuentes Ferrer; Juan Luis Rodríguez Hermosa (PLoS ONE, 2025)
Objective This study aimed to evaluate clinical control in chronic obstructive pulmonary disease (COPD), the consequences in terms of treatment decisions, and their potentially associated factors during follow-up of patients in real-life clinical practice. Methods EPOCONSUL 2021 is a cross-sectional audit that evaluated the outpatient care provided to patients with a diagnosis of COPD in respiratory clinics in Spain and multivariable logistic regression models to assess the relationships between clinical control and clinical inertia. Results 4225 patients from 45 hospitals in Spain were audited. Clinical control was analyzed in 1804 (42.7%) patients who met all the Spanish COPD Guidelines (GesEPOC) criteria. 49.1% of patients were classified as uncontrolled, and 42.2% of patients disagreed with the level of control determined by their doctor, which was reported as good during the visit. There was therapeutic inertia (TI), in other words not making any change or taking any action in the treatment of COPD, in 68.4% of uncontrolled patients and no action was taken during the visit for 9.1% of uncontrolled patients. Factors associated with TI in uncontrolled patients were disagreement with the degree of control reported by the doctor who performed the examination ☯physician classifies and reports disease as controlled versus uncontrolled, OR: 3.37 (2.33–4.88), p<0.001] and having a lower burden of associated comorbidities ☯Charlson comorbidity index ≥3 versus <3, OR 0.8 (0.1–3.0), p = 0.014]. The probability of disagreeing with the physician’s classification of the degree of COPD control in uncontrolled patients was lower in patients with severe exacerbations ☯OR 0.3 (0.17–0.78), p = 0.009] and those with more exacerbations in the last year ☯OR 0.6 (0.4–0.9), p = 0.019]. Conclusions Therapeutic inertia exists in more than half of uncontrolled patients and is more likely when there is disagreement with the assessment of the physician responsible for the visit, who reported there being good disease control, a situation that was more likely in patients with less history of exacerbations.